Flash Flood in Madeira Island in autumn 2012 - Couto, Flavio (2014)
Madeira (32º75'N and 17º 00'W) is a Portuguese mountainous island with the highest peaks above 1800 m, where after the catastrophe of 20 February 2010, which has shown to be vulnerable to the flood occurrences from significant socio-economical losses. Using ground observations and the MESO-NH model, this study investigates the main atmospheric aspects related to the flash flood and landslides occurrences on 05 November 2012 in the island. The period between 25 October and 06 November 2012 have been considered in the analysis. The numerical simulations are performed using different configurations, with a single domain of 25 km horizontal resolution and using grid nesting technique with 9, 3 and 1 km resolution. During this period, two main events were chosen based on rain gauge data analysis, to be simulated at high resolution (1km): 30 October and 05 November, when the highest amounts of precipitation in Madeira's highlands and landslides were observed, respectively. Previous studies show that the heavy rainfall events in Madeira depend on both synoptic and mesoscale features, justifying the simulations in different resolutions. The accumulated precipitation simulation pointed out the prominent role of orography in the intensification of precipitation over the island. The possibility of severe weather development was confirmed from some instability indices obtained from radiosonde observations, despite the CAPE index, which indicated a weak instability environment. On the other hand, large-scale environment was characterized by the development of extratropical cyclones near the island, where the frontal structure acting over Madeira's archipelago is evident. A remarkable feature is the fact that on 30 October, coupled to a frontal system, the main moisture source in low-levels was related to an atmospheric river structure passing over the island.